Hot runner system design for injection molds - A. Nisar Ahmed (2008)
The objective of this study is to develop a Hot Runner System Design Guide for Mold designers. Current Hot Runner System Design practice was studied and is described. A new design process is proposed to shorten lead times and to improve the quality of designs. The main design parameters of hot runner systems are described and their impacts on the final plastic product are discussed. A Hot Runner System Design Guide has been developed and described. The thesis concludes by briefly discussing how the Design Guide can be integrated with commercial CAD software. The needs of various modules required for a total computer aided system for injection mold design are also mentioned.